2008
DOI: 10.1103/physrevlett.100.166802
|View full text |Cite
|
Sign up to set email alerts
|

Charge Response Function and a Novel Plasmon Mode in Graphene

Abstract: Polarizability of non-interacting 2D Dirac electrons has a 1/ √ qv − ω singularity at the boundary of electron-hole excitations. The screening of this singularity by long-range electron-electron interactions is usually treated within the random phase approximation. The latter is exact only in the limit of N → ∞, where N is the "color" degeneracy. We find that the ladder-type vertex corrections become crucial close to the threshold as the ratio of the n-th order ladder term to the same order RPA contribution is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 15 publications
2
100
0
1
Order By: Relevance
“…In addition, the spectrum of electron-hole excitations can be modified by excitonic effects: the Coulomb attraction between the electron and the hole lowers the energy of the excitation with respect to its non-interacting value, so that the singularity in I D should be at a lower frequency. The author is aware of only one study of excitonic effects in the optical response of monolayer graphene; within the Dirac model it was shown that excitonic effects result in a weak feature at the border of the electron-hole continuum [33]. Their importance for optical excitation of electrons near the M point of the first Brillouin zone remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the spectrum of electron-hole excitations can be modified by excitonic effects: the Coulomb attraction between the electron and the hole lowers the energy of the excitation with respect to its non-interacting value, so that the singularity in I D should be at a lower frequency. The author is aware of only one study of excitonic effects in the optical response of monolayer graphene; within the Dirac model it was shown that excitonic effects result in a weak feature at the border of the electron-hole continuum [33]. Their importance for optical excitation of electrons near the M point of the first Brillouin zone remains to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamical polarization properties were studied in Ref. 25, where the vertex diagrams were found to have logarithmically singular contributions near the threshold ω ∼ vq, leading to the possibility of a plasmon mode.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, this zero band gap semimetal supports significant light‐matter interaction of high efficiency, and shows undispersed absorb properties 55, 56, 57. Furthermore, the plasmonic condition can be modified by electrical and chemical doping or hybridizing graphene with other 2D materials or traditional plasmonic nanostructures 58, 59. Among several kinds of intrinsic plasmon modes in graphene, there is longitudinal mode which is also defined as transverse magnetic mode and the polarizing electric field is parallel to the wave vector q .…”
Section: Plasmonic Properties Of 2d Nanomaterialsmentioning
confidence: 99%